Hollow parties and their movement-ization: The populist conundrum. (December 2019) - Cohen, Jean L.
This article focuses on the relationship between social movements and political parties in the context of populist challenges to constitutional democracy. There are many reasons for the current plight of democracy but I focus here on one aspect: the decline of mainstream political parties, the emergence of new forms of populist movement parties and the general crisis of political representation in long consolidated Western democracies. This article analyses the specific political logic and dynamics of social movements – the logic of influence, and distinguishes it from that of political parties – the logic of power. It addresses transformations in movements, parties and their relationships. It looks at the shifts in movement and party types that constitute the political opportunity structure for the emergence of new populist movement party forms and relationships, focusing on the hollowing out and movement-ization of political parties. Contemporary populist movement parties are not the cause of the hollowing out or movement-ization of political parties. Rather they are a response to the crisis of political representation exemplified by hollow parties and cartel parties. But it is my thesis that thanks to its specific logic, populism fosters the worst version of movement party relationships, undermining the democratic functions of both.